2020
DOI: 10.1111/1440-1681.13261
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporters and diabetic nephropathy: Is there a link with toll‐like receptors?

Abstract: The incidence of diabetes mellitus (DM) has increased alarmingly over the last decades. Despite taking measures aimed at controlling hyperglycaemia and blood pressure, the rate of end‐stage renal disease (ESRD) is continually growing. Upon increased amounts of advanced glycation end products (AGEs) and their correspondent receptors (RAGEs), AGE‐RAGE axis is over‐activated in DM, being the first step in the initiation and propagation of inflammatory cascades. Meanwhile, HMGB1, released from damaged cells in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…GLUT 1 in particular is upregulated in pro-inflammatory macrophages to support the upregulation of glycolytic metabolism ( 48 , 179 ). Macrophages can also accumulate glucose against a concentration gradient in a glucose-deprived environment using sodium-glucose transporters ( 180 , 181 ). However, GLUT 1 is the major transporter of glucose into monocyte/macrophages and is relatively insulin independent, i.e., uptake is determined by the extracellular glucose concentration.…”
Section: Leukocyte Activation In Diabetes—what Is the Evidence?mentioning
confidence: 99%
“…GLUT 1 in particular is upregulated in pro-inflammatory macrophages to support the upregulation of glycolytic metabolism ( 48 , 179 ). Macrophages can also accumulate glucose against a concentration gradient in a glucose-deprived environment using sodium-glucose transporters ( 180 , 181 ). However, GLUT 1 is the major transporter of glucose into monocyte/macrophages and is relatively insulin independent, i.e., uptake is determined by the extracellular glucose concentration.…”
Section: Leukocyte Activation In Diabetes—what Is the Evidence?mentioning
confidence: 99%
“…However, if AGEs are not metabolized, they deposit in the kidneys and bind to AGE receptors (RAGE), which cause various pathological changes, including oxidative stress, apoptosis, and inflammation ( 35 ). The AGE and RAGE axis play a role in diabetic nephropathy ( 36 , 37 ). In the present study, adding AGE-Tf (33.3 mM) and AGE-Tf (500 mM) to stimulate HK-2 in vitro showed that glycated-Tf promoted apoptosis of HK-2 cells and weakened its antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end-products (AGEs) are heterogeneous compounds that are created when proteins, lipids, or nucleic acids are glycated during hyperglycemia without the use of an enzyme. A novel risk factor for the development of DN has been discovered: the buildup of AGEs in peripheral nerves [ 24 ]. The gold standard for AGE assessments in tissues is tissue biopsy.…”
Section: Reviewmentioning
confidence: 99%